The policy menu for school lunches: Options and tradeoffs in expanding free school meals in England - Jonathan Cribb; Christine Farquharson; Andrew McKendrick; Tom Waters (Institute for Fiscal Studies (IFS), 2023)
Of the 8.4 million children in English state schools, 3.4 million are eligible to get a free meal at school each day. Just under 2 million of these children are eligible through the means-tested system, which includes children whose families are receiving certain means-tested benefits and on very low incomes. Since 2014, all children in the first three years of primary school - Reception, Year 1 and Year 2 - have been eligible for free school meals. Options to expand free school meals have been frequently discussed. London Mayor Sadiq Khan recently announced that, in 2023-24, all primary-age children in state schools in London will be eligible for a free school meal, expanding eligibility by 270,000 pupils beyond the 550,000 who are already eligible. Other proposals suggest expanding entitlement to free school meals by increasing the earnings threshold for eligibility from the current 7,400 a year (after tax). For example, the National Food Strategy suggested a threshold of 20,000 a year after tax. In this report, we discuss the options and trade-offs in expanding free school meals in England. We focus on several potential reforms that would expand the generosity of the free school meal system, either by increasing the value of free school meals or by expanding eligibility to a wider range of pupils, and set out the costs of these policies, their distributional impacts, and their potential effect on parents' work incentives.
Keywords: 330; Poverty; inequality and social mobility; Taxes and benefits; Benefits; Distributional effects; Government spending; Poverty; Nutrition; Universal credit; Working age benefits